Maternal risk factors for gastroschisis: A population‐based case–control study. Issue 13 (14th May 2020) - Raitio, Arimatias; Tauriainen, Asta; Leinonen, Maarit K; Syvänen, Johanna; Kemppainen, Teemu; Löyttyniemi, Eliisa; Sankilampi, Ulla; Gissler, Mika; Hyvärinen, Anna; Helenius, Ilkka
Abstract: Background: Gastroschisis is an open abdominal wall defect with low mortality but significant morbidity. The prevalence has been increasing worldwide for the past decades. Several risk factors for gastroschisis have been identified, but no clear reason for increasing prevalence has been found. In our study, we aimed to assess and identify maternal risk factors for gastroschisis. Methods: In our nationwide register‐based case–control study, we identified all gastroschisis cases in the Finnish Register of Congenital Malformations from 2004 to 2014. Information on drug prescriptions and purchases was received from Drugs and Pregnancy database. Five healthy age‐matched controls from the same geographical region were randomly selected for each case. Conditional logistic regression was used to evaluate different risk factors. Results: One‐hundred‐eighty‐eight cases of gastroschisis were identified and compared with 910 matched controls. Nulliparity was a significant risk factor for gastroschisis, aOR 2.00 (95% CI 1.29–3.11) whereas obesity was protective, aOR 0.35 (95% CI 0.15–0.83). Smoking appeared to increase the risk for gastroschisis, aOR 1.32 (95% CI 0.88–1.97). The mean maternal age of newborns with gastroschisis was significantly lower than average ( p  <.001). Conclusion: As in previous studies, nulliparity and young maternal age were significant risk factors for gastroschisis. Maternal obesity significantly reduced the risk of gastroschisis regardless of maternal age and gestational diabetes.